Evaluation of Online English Learning Programs During the Covid 19 Pandemic Using the Cipp Model - Salim, Herli; Suryadi, Suryadi (IJECA (International Journal of Education and Curriculum Application), 2022)
This study aims to determine: (1) the effectiveness of online English learning program implementation during the COVID-19 pandemic in terms of the context component (X1; (2) the effectiveness of online English learning program implementation during the COVID-19 pandemic in terms of the input component (X2); and (3) the effectiveness of online English learning program implementation during the COVID-19 pandemic in terms of the output component (X3). (4) the effectiveness of the online English learning program implementation during the COVID-19 pandemic from the product component; (5) the effectiveness of the implementation of online English learning programs during the COVID-19 pandemic in terms of the context (X1), inputs, processes, and product components; and (6) obstacles that impede the implementation of online English learning programs during the Covid-19. Data was gathered through the use of a questionnaire completed by 250 respondents. And the research sample consisted of 50 students chosen at random. after the data analysis results are transformed to a T-score and then enter the Glickman quadrant for evaluating the online English learning program's performance. The findings indicated that the CIPP score on the Glickman Quadrant (-+++) reflects a successful implementation of the online English learning program. They discovered a number of impediments to online English instruction, including the following: 1) Restrictions on media, network, or internet signals, as well as student internet quotas; and provision of customized internet quotas to assist students with specific learning requirements. 2) Student dissatisfaction with online education and a desire to meet in person on a permanent basis, comparable to the pre-pandemic era. 3) Due to the pandemic's prolonged presence, students' passion for studying has waned.